EFL TEACHERS’ UNDERSTANDING IN DEVELOPING LESSON PLAN - Annisa Putri (Indonesian EFL Journal, 2016)
This research attempts to find out EFL teachers’ understanding of lesson plan and the development along with problems the teachers faced in developing lesson plan. The researcher used two data collection techniques; interview and analyzing the lesson plan developed by four EFL teachers. The interview results revealed that all participants understand about the lesson plan as well as its development and understand about the elements that should be included as parts of lesson plan, but, unfortunately, the teachers could not understand the system of learning assessment. They thought that it is too complicated because they should provide one system of learning assessment along with the rubric of assessment. On the other hand, the result of lesson plan analysis showed that all participants understand how to develop lesson plan by stating all elements of lesson plan in accordance with the requirements stated in the Regulation of Ministry of Education and Culture No. 103 in 2014. The problems found are when the teachers did not state learning purposes, even two of the teachers stated that learning indicator is similar with learning purposes. Another problem is found when they did not include the assessment rubric. Then, the other problem is found when they were asked about the implementation of scientific approach. Scientific approach is a new thing for them to be applied as the approach consists of observing, questioning, associating, collecting, and communicating.Keywords: lesson plan, lesson plan development, 2013 curriculum